Measles and rubella elimination: learning from polio eradication and moving forward with a diagonal approach - James L. Goodson; James P. Alexander; Robert W. Linkins; Walter A. Orenstein (Taylor & Francis Group, 2017)
Introduction: In 1988, an estimated 350,000 children were paralyzed by polio and 125 countries reported polio cases, the World Health Assembly passed a resolution to achieve polio eradication by 2000, and the Global Polio Eradication Initiative (GPEI) was established as a partnership focused on eradication. Today, following eradication efforts, polio cases have decreased >99% and eradication of all three types of wild polioviruses is approaching. However, since polio resources substantially support disease surveillance and other health programs, losing polio assets could reverse progress toward achieving Global Vaccine Action Plan goals. Areas covered: As the end of polio approaches and GPEI funds and capacity decrease, we document knowledge, experience, and lessons learned from 30 years of polio eradication. Expert commentary: Transitioning polio assets to measles and rubella (MR) elimination efforts would accelerate progress toward global vaccination coverage and equity. MR elimination feasibility and benefits have long been established. Focusing efforts on MR elimination after achieving polio eradication would make a permanent impact on reducing child mortality but should be done through a 'diagonal approach' of using measles disease transmission to identify areas possibly susceptible to other vaccine-preventable diseases and to strengthen the overall immunization and health systems to achieve disease-specific goals.